Production of antibacterial agent from Streptomyces griseus by using Semi Solid Fermentation - Nader, Mohammed I. (Journal of the Faculty of Medicine Baghdad, 2009)
Backround: The Solid state fermentation has several advantage including absence of free water , reduced volume of production media utilized for high products and the relatively low costs of production. Methods: Thirty local isolates of soil obtained from Genetic Engneering and Biotechnology Institute. Nutrient agar was used to growth strains examination to antibacterial agent and Wheat bran and fish meal were used in combination (0-100%of each )and divided in 10 gm lost /flask . Each flask is inoculated with different numbers of Streptomyces spores and incubated for 5 days at 28°C, then the supernet was extracted and were assayed as antibacterial Results: The ability of 30 local isolates of Streptomyces and the standard strain S.griseus for antibacterial production were tested by grow in Muller Helton agar. The later isolate (standard isolates) showed highest antibacterial activity with inhibitory effect of (30 mm,24 mm ,20mm, 18mm ) compared with local isolates (S1 ,S2 , S3 ) resectively Conclusion: only two soil isolates (among 30 isolates) and standard isolates of Streptomyces griseus were appears able to produce antibacterial agent under optimum condition . The optimum condition for the production of antibacterial is solid state fermentation included the use of wheat bran hydrate with distilled water pH=8 and the optimum hydration ratio was 1:3 (w:v) with an inoculum size of 6x109 spores/flask ( 10 gm wheat bran ) and incubation for 5 days at 28°C.